Web‐Based Model for Predicting Time to Surgery in Young Patients with Familial Adenomatous Polyposis: An Internally Validated Study. (December 2018) - Sarvepalli, Shashank; Burke, Carol A.; Monachese, Marc; Lopez, Rocio; Leach, Brandie H.; Laguardia, Lisa; O'Malley, Margaret; Kalady, Matthew F.; Church, James M.
Abstract : INTRODUCTION: The timing of prophylactic colorectal surgery in patients with familial adenomatous polyposis (FAP) is based on the immediacy of the colorectal cancer risk. The ability to predict the need for surgery may help patients and their families plan in the context of life events and CRC risk. We created a model to predict the likelihood of surgery within 2 and 5 years of first colonoscopy at our institution. METHODS: A single institution hereditary colorectal syndrome (Cologene TM ) database was interrogated for all patients with FAP having a deleterious APC mutation. Patients with first colonoscopy after age 30 and before year 2000 were excluded. Cox regression analysis was done to assess multiple factors associated with surgery, followed by stepwise Cox regression analysis to select an optimal model. Receiver operator curve (ROC) analysis was performed to assess the model. RESULTS: A total of 211 (53% female) patients were included. Forty‐five percent underwent surgery after an average of 3.8 years of surveillance. The final model was created based on initial clinical characteristics (age, gender, BMI, family history of desmoids, genotype‐phenotype correlation), initial colonoscopic characteristics (number of polyps, polyp size, presence of high‐grade dysplasia); and on clinical events (chemoprevention and polypectomy). AUC was 0.87 and 0.84 to predict surgery within 2 and 5 years, respectively. The final model can be accessed at this website: http://app.calculoid.com/#/calculator/29638 . CONCLUSION: This web‐based tool allows clinicians to stratify patients' likelihood of colorectal surgery within 2 and 5 years of their initial examination, based on clinical and endoscopic features, and using the philosophy of care guiding practice at this institution.